INFLASI KOMODITAS ADMINISTERED PRICE DAN DAYA BELI MASYARAKAT SELAMA PANDEMI COVID-19: STUDI KASUS PROVINSI ACEH - Diana, Asri; Fitriyani; Purnawa Sari, Yunidar; Rizkina, Azka (Universitas Mataram, 2023)
This study aims to analyze the effect of inflation of administered prices, namely the price of fuel, LPG, electricity, and water on people's purchasing power during the Covid-19 pandemic in Aceh Province by looking at changes in price elasticity and elasticity of opinion. This study uses secondary data in the form of a March 2021 cross-section obtained from the National Socioeconomic Survey (SUSENAS). With the Almost Ideal Demand System (AIDS) analysis model, the results showed that people's purchasing power during the Covid-19 pandemic in Aceh Province had a significant and positive effect on commodity prices themselves and cross-commodity prices, while expenditure was negative. Furthermore, the results of the calculation of the elasticity value show that in 2021 people's purchasing power is inelastic in four administered prices commodities with their price elasticity of negative value, especially in electricity, fuel, and PAM water commodities. While cross-price elasticity is positive. The income elasticity has a negative value in LPG and PAM water commodities, and a positive value in electricity and fuel commodities. Therefore, the government needs to maintain the price stability of goods, especially administered prices to improve the welfare of its people.